Marco teórico para un análisis integral de los derechos humanos y fundamentales - Parra-Quemba, William Javier (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The objective of this work was to show that the construction of the theoretical framework of human rights has revolved around four main categories of analysis: the concept, the foundation, the materialization and the responsibilities for the protection and violation of the same. However, for more than a decade, studies aimed at the construction and solution of practical social problems, which affect fundamental, social and collective rights, have been prioritized. On the other hand, the activities of research groups and organizations of human rights defenders converge in the need to apply.